Cyclopropenone-masked dibenzocyclooctyne end-functionalized polymers from reversible addition-fragmentation chain transfer polymerization. (7th April 2017) - Qu, Lin; Wu, Ying; Sun, Peng; Zhang, Ke; Liu, Zhengping
Abstract: Functional reversible addition-fragmentation chain transfer polymerization (RAFT) agent was developed to have a cyclopropenone-masked dibenzocyclooctyne end group. RAFT polymerization was then explored on three typical types of vinyl monomers in free radical polymerization such as styrene, methyl methacrylate, and tert -butyl acrylate. The living polymerization behaviors were demonstrated for all three cases, which guaranteed the production of well-defined polystyrene, poly (methyl methacrylate), and poly ( tert -butyl acrylate) end-functionalized with cyclopropenone-masked dibenzocyclooctyne groups from the convenient RAFT polymerization technique. Under UV irradiation, the cyclopropenone-masked dibenzocyclooctyne end group could be quantitatively changed to dibenzocyclooctyne clickable group, which was widely used in the metal-free strain-promoted azide-alkyne cycloaddition (SPAAC) click reaction. Subsequently, using the dibenzocyclooctyne end-functionalized polymers as building blocks, a practical and efficient metal-free method was developed for the formation of topological polymers including block and bottlebrush polymers based on the SPAAC click reaction. Graphical abstract: Highlights: Cyclopropenone-masked dibenzocyclooctyne end functionalized RAFT initiators. RAFT of methacrylates, styrenics, and acrylates. UV-induced SPAAC click chemistry.